If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(2 + -1j) + 3(5 + 2j) = 2(7 + -2j) + -4(1j + -1) (2 * 9 + -1j * 9) + 3(5 + 2j) = 2(7 + -2j) + -4(1j + -1) (18 + -9j) + 3(5 + 2j) = 2(7 + -2j) + -4(1j + -1) 18 + -9j + (5 * 3 + 2j * 3) = 2(7 + -2j) + -4(1j + -1) 18 + -9j + (15 + 6j) = 2(7 + -2j) + -4(1j + -1) Reorder the terms: 18 + 15 + -9j + 6j = 2(7 + -2j) + -4(1j + -1) Combine like terms: 18 + 15 = 33 33 + -9j + 6j = 2(7 + -2j) + -4(1j + -1) Combine like terms: -9j + 6j = -3j 33 + -3j = 2(7 + -2j) + -4(1j + -1) 33 + -3j = (7 * 2 + -2j * 2) + -4(1j + -1) 33 + -3j = (14 + -4j) + -4(1j + -1) Reorder the terms: 33 + -3j = 14 + -4j + -4(-1 + 1j) 33 + -3j = 14 + -4j + (-1 * -4 + 1j * -4) 33 + -3j = 14 + -4j + (4 + -4j) Reorder the terms: 33 + -3j = 14 + 4 + -4j + -4j Combine like terms: 14 + 4 = 18 33 + -3j = 18 + -4j + -4j Combine like terms: -4j + -4j = -8j 33 + -3j = 18 + -8j Solving 33 + -3j = 18 + -8j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '8j' to each side of the equation. 33 + -3j + 8j = 18 + -8j + 8j Combine like terms: -3j + 8j = 5j 33 + 5j = 18 + -8j + 8j Combine like terms: -8j + 8j = 0 33 + 5j = 18 + 0 33 + 5j = 18 Add '-33' to each side of the equation. 33 + -33 + 5j = 18 + -33 Combine like terms: 33 + -33 = 0 0 + 5j = 18 + -33 5j = 18 + -33 Combine like terms: 18 + -33 = -15 5j = -15 Divide each side by '5'. j = -3 Simplifying j = -3
| 3(x+88)= | | 2g+14=-8 | | -4y=6-6x | | 4p-(3p+2r-4)+3-r= | | 4s^2+3s-15=0 | | 17=3 | | 10x-3x+(-5x)= | | 15+5x=5(x+3) | | 8+c=13 | | 4p-(3p+2r-4)= | | 9x^8-72x^6=0 | | v-7=-12 | | 20x-24y=120 | | -4y+2x+8=0 | | x=100-3x | | x-14=-32 | | 0.05x+1.02x= | | 3-2*=11 | | 7+3x=3x+10 | | 19+b=17 | | -q-11=2+4 | | x^4+-15x^2+56=0 | | 2x-3=4x-2 | | 2j+5=6h | | 6a-4a=-36 | | (7x)-(2x)= | | 81=-3(-6+3n) | | 5x+6=10x-94 | | -6y=15-3x | | x=9x+16 | | P(x)=8x-1600 | | r-10=-15 |